KETERLIBATAN KOALISI MINYAK SAWIT SWISS DALAM DIPLOMASI EKONOMI PERUNDINGAN INDONESIA-EUROPEAN FREE TRADE ASSOCIATION COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT PERIODE 2011-2018 - Giffary Salsha Al Fajrin (2022)
Discussions related to palm oil are complex because they are not only related to trade, but also aspects of sustainable development have often been associated with palm oil. As a strategic export commodity for Indonesia, the government always tries to include CPO trade agreements in the trade agreements that are formulated, including the Indonesia-EFTA CEPA. However, in the midst of the government's efforts, several Swiss national NGOs in the form of NGO coalition asked the government to exclude the CPO agreement from the trade agreement. This study aims to understand and explain the involvement of NGOs in the economic diplomacy of the Indonesia-EFTA CEPA negotiations within the framework of International Relations. The research method used by the author is descriptive qualitative research method with a case study approach. In this study, the author used three data collection methods, namely interview, document-based, and internet-based methods to obtain primary and secondary data. The data analysis technique chosen is Miles and Huberman's data analysis technique which consists of data reduction, data presentation, and verification and conclusion drawing. Based on the results of data analysis that has been carried out in this study, the author sees that the form of NGO involvement in the Indonesia-EFTA CEPA negotiations regarding the CPO agreement can be divided into two, NGOs as government consulting partners, and NGOs as government pressure groups. As consulting partners, NGOs hold meetings and discussions as a form of lobbying to get involved in the CPO trade agreement negotiations. Meanwhile, as a pressure group, NGOs involve massive public participation to convey their positions and demands which is to exclude CPO free trade from Indonesia-EFTA CEPA.